PEMBELAJARAN BERBASIS PRODUKSI UNTUK PENINGKATAN KOMPETENSI MEMBUAT GAMBAR KERJA TEKNIK MESIN SISWA SMK - Pardjono Pardjono (Jurnal Pendidikan Vokasi, 2011)
This study is aimed at improving quality of learning process of Mechanical Drawing by employing Production Based Training to achieve mechanical drafter   competency.   Consecutively   this   research   will   also   develop   teacher's professionalism  in managing  learning process  of  Mechanical  Drawing  at  SMK  Sf Mikael. This classroom action research was conducted in SMK St. Mikael Surakarta. Grade XI was assigned to be subject of this research. Two collaborators were assigned to  back  up and  assist  the researchers  to  monitor  the  effects  of  action  on student competency  in mechanical  drawing.  The changes due  to  the  action  are  monitored through  observation  by  involving  the  two  collaborators.  The  collected  data  was analyzed  descriptively. The  data  analysis  resulted  in  the following   findings:    (a) production  based learning  improves students achievement  in reaching  the minimum mastery  criteria  on  Mechanical  Drawing  and  more  specifically  improves  student competency  in producing  machining industries standardized  of Mechanical  Working Drawing, (b) a process of expertise acquition in mechanical working drawing through combination of constructivism learning principles, behaviorism, situated learning and cognitive apprenticeship .. (c) the production-based  learning increases students' ability behave discipline and attitude toward mechanical drawing, and  (d) production based learning   was implemented through classroom discussion on the mechanical drawing principles, its implementation on working drawings, integrating knowledge on components stradard as well as production process into working drawing.